Metode Bernyanyi dalam Pembelajaran Bahasa Arab Untuk Anak Usia Dini - Muhammad Radhi Al Mardhi; Fauziah Bachtiar (CV. ULIL ALBAB CORP, 2024)
Singing is one of the effective methods in the language learning process, especially in learning Arabic as a foreign language for early childhood. The purpose of this study is to identify the special features of the singing method in the Arabic language learning process for early childhood. The type of research used is qualitative research with a literature review method which means analyzing journals and books related to the singing method in learning Arabic for early childhood. The results and conclusions of this study state that there are five special features of the singing method in learning Arabic for early childhood: 1) The singing method can support three main elements in learning Arabic for early childhood, namely phonological elements (ashwat) or pronunciation, morphological (mufradat) or vocabulary, and syntax (nahwiy) or rules. 2) The singing method also supports four mandatory Arabic language skills, namely receptive skills, namely listening (istima') and reading (qira'ah). And productive skills, namely speaking (kalam) and writing (kitabah) 3). The singing method can make quiet children active and enthusiastic. 4) The singing method becomes a solution to boredom which is one of the main enemies in the process of learning Arabic as a foreign language. 5) The singing method becomes a means of understanding religion and character education or exemplary behavior.